Not so Intimate Instagram: Images of Swedish Political Party Leaders in the 2018 National Election Campaign. Issue 2 (3rd April 2023) - Grusell, Marie; Nord, Lars
Abstract: The visual components of political communication are closely related to the ongoing personalization of politics. Not only do the media focus their stories on candidates and leaders, but also the parties' own work with the electoral campaigns and political propaganda have an increasing focus on the individual candidates and leaders. This study focuses on how political party leaders chose to use visual images in their self-presentation on Instagram during the 2018 general election in Sweden. This is done through a quantitative content analysis of party leaders' posts during the last three weeks before Election Day. The results do not confirm an increasing level of personalization of politics. Party leaders were visually exposed in an innovative way, but still mainly within rather predictable campaign contexts. General social media standards have been developed by political parties also on this platform. When applying to these standards branding and long-term party strategy considerations seem to be more important than possible short-term effects of exposing surprising personal and emotional characteristics of the party leader.